Georgia : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report provides an assessment of accounting, financial reporting and auditing requirements and practices within the enterprise and financial sectors in Georgia. The report uses International Financial Reporting Standards (IFRS), International Standards on Auditing (ISA) and draws on international experience and good practices in the field of accounting and audit regulation, including in European Union (EU) Member States, to assess the quality of financial information and make policy recommendations. The financial sector in Georgia is growing rapidly but remains largely underdeveloped, partly due to the lack of funding from local deposits and limited access to funding from foreign financial institutions. This report focuses on the principal reason for continuing with further reforms; specifically, on the benefits that the proposed reforms will bring to Georgia and its citizens. In this context, this report sketches policy recommendations to enhance the quality of corporate financial reporting and foster a financial reporting platform conducive to sustainable private and financial sector growth, thus increasing access to global financial markets and other tools of a market economy. The report specifically recommends: measures to encourage preparers of financial statements in Georgia to improve their accounting knowledge; that the GFPAA establish a recognized qualification at a lower level than its full qualification; that the GFPAA work to bring the quality of its Georgian language ACCA-based qualification up to the standard of the English language; that the GFPAA work closely with Georgian universities to coordinate syllabuses; and that key operational staff from regulators such as the NBG, NSC and SISSG are seconded to similar agencies abroad for 'on the job' training.